(untitled) (The Research of Medical Science Review, 2025)
Background: Thyroid disorders are among the most common endocrine conditions worldwide, with a significant prevalence in Pakistan. Thyroidectomy, a frequently performed surgical procedure, requires meticulous hemostasis due to the gland's rich vascular supply and proximity to critical structures. This randomized study compares the incidence of post-operative hypocalcemia in total thyroidectomy patients undergoing the LigaSure technique versus the conventional clamp-and-tie method. Materials and Methods: This randomized controlled trial compared the LigaSure technique with the conventional clamp-and-tie method in total thyroidectomy patients to assess postoperative hypocalcemia. Conducted at the Federal Government Polyclinic Hospital, Islamabad, from January to December 2024, 100 patients were enrolled and randomly assigned to either technique. Surgical outcomes, including operative time and calcium levels, were analyzed using SPSS version 23.0, with statistical significance set at p ≤ 0.05. Results: This study included 100 total thyroidectomy patients, with 50 in the Conventional Clamp-and-Tie group and 50 in the LigaSure group. The LigaSure technique significantly reduced operative time (p < 0.001) and postoperative hypocalcemia incidence (p = 0.038). Binary logistic regression confirmed a lower risk of hypocalcemia with LigaSure (OR 3.173, p = 0.048), independent of other factors. Conclusion: The LigaSure vessel-sealing system significantly reduces operative time and postoperative hypocalcemia compared to the conventional clamp-and-tie technique in total thyroidectomy, demonstrating its superiority in surgical outcomes.